2021
DOI: 10.3389/fped.2021.665655
|View full text |Cite
|
Sign up to set email alerts
|

BMI Trajectories During the First 2 Years, and Their Associations With Infant Overweight/Obesity: A Registered Based Cohort Study in Taizhou, China

Abstract: Objective: The purpose of this study was to identify trajectories of body mass index (BMI) in toddlers from birth to 2 years old and examine their association with infantile overweight/obesity.Methods: Data were collected from 19,054 children born in any hospital or community healthcare center in Taizhou, China from 2018 to 2019 with at least three BMI measurements after birth. The Latent Class Growth Mixture Model was used to identify distinct BMI trajectories during the first 2 years of infants. Multiple log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…It was suggested that the maternal weight represents the nutritional environment of the fetus. The fetus develops a specific adipose tissue memory system to adapt to the nutritional environment, which could profoundly affect its future nutritional status (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the maternal weight represents the nutritional environment of the fetus. The fetus develops a specific adipose tissue memory system to adapt to the nutritional environment, which could profoundly affect its future nutritional status (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation with formula during the first week of life reprograms normal weight trajectory, leading to a greater risk for obesity by the age of two years [ 1 2 ]. Breastfeeding is shown to prevent the “obese phenotype”, with longer durations of breastfeeding associated with decreased growth acceleration rates, and thus, decreased likelihood of being obese or overweight [ 4 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, BMI trajectory, based on the latent class growth model (LCGM), utilizing at least three repeated measures in a longitudinal cohort can provide additional information about BMI ( Mattsson et al, 2019 ). A study identified distinct BMI trajectories during the first 2 years of infants and showed that infants in the middle and upper trajectory groups were more likely to suffer excessive weight/obesity ( Zhang et al, 2021 ). Besides, many studies have confirmed that different BMI growth trajectories contribute to different risks of obesity, cardiovascular diseases, and metabolic syndrome ( Rolland-Cachera et al, 1984 ; Braun et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%